Village Fund Utilization Based on Good Governance Principles: Empirical Evidence from Indonesia (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study examines the influence of good governance principles on village fund utilization effectiveness in Indonesia. Using a quantitative approach with Structural Equation Modeling - Partial Least Squares (SEM-PLS), we analyze data from 385 village officials across five provinces in Indonesia. The research integrates stewardship theory and agency theory to explain how transparency, accountability, participation, and rule of law affect village fund management performance. Results demonstrate that transparency (β=0.342, p<0.01) and accountability (β=0.287, p<0.01) significantly enhance village fund utilization effectiveness, while participation (β=0.219, p<0.05) shows moderate influence. Rule of law (β=0.156, p>0.05) does not significantly affect fund utilization, suggesting implementation challenges. The model explains 68.4% variance in village fund utilization effectiveness (R²=0.684). This study contributes to governance literature by providing empirical evidence from emerging economies and offers practical implications for policymakers to strengthen village-level financial management through enhanced transparency mechanisms and accountability systems. The findings highlight the critical role of good governance in achieving sustainable rural development goals.